Acute Symptomatic Focal Seizure with Todd’s Paralysis as an Initial Presentation of Acute Stroke in a Non-epilepsy Centre, A Case report - Hana Maizuliana Solehan; Tan Wei Ming; Fatimah Zanirah; Nur Ezzaty Mohammad Kazmin; Sarah Zulaikha Samad; Nor Safiqah Sharil; Mohd Firdaus A Bakar; Norazinizah Ahmad Miswan (USIM Press, 2024)
Conference Date: 7th October 2021 https://nhs2021.usim.edu.my